The Impact of Transformational Leadership on Organizational Innovation and Job Performance: The Mediating Roles of Management Control Systems and Employee Engagement - Moray, Sachin L; Dias, Beena (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Purpose: This study investigates the impact of transformational leadership (TL) on organizational innovation (OI) in resource-constrained tier-two districts, examining the mediating roles of employee engagement (EE) and management control systems (MCS). Design/methodology/approach: A cross-sectional quantitative design was employed, collecting survey data from managers and employees across various sectors in tier-two districts of Karnataka, India. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied using SmartPLS, with validity checks including HTMT, Fornell–Larcker criterion, and variance inflation factors. Findings: Results reveal a significant direct relationship between TL and OI, with EE serving as a strong mediator in this linkage. Conversely, MCS did not exhibit a significant mediating effect. These findings highlight that in environments with limited resources and competitive pressures, people-centric approaches that enhance employee vigor, dedication, and absorption are more effective in fostering innovation than reliance on formal control mechanisms. Research limitations/implications: The cross-sectional design limits causal inference, and the geographic focus on tier-two districts may affect generalizability. Future research should consider longitudinal approaches and explore interaction effects between EE and MCS in varied contexts. Practical implications: Organizations in similar settings should prioritize leadership development programs that cultivate employee engagement to drive innovation. Emphasis should be placed on motivating and involving employees rather than depending solely on control systems. Originality/value: This study contributes to TL theory by demonstrating the differential effectiveness of mediating mechanisms across contexts, offering a context-sensitive perspective on innovation in underexplored geographical and economic environments.